POLEMIK ANTARA PENERIMAAN DAN PENOLAKAN VAKSINASI KANAK-KANAK: ANALISIS DARI PERSPEKTIF ISLAM: Polemics between Acceptance and Rejection of Children’s Vaccination: An Analysis from Islamic Perspective - Tengku Md Fauzi, Tengku Fatimah Azzahra; Mohd Razif, Nor Fahimah; Ramli, Mohd Anuar (Jurnal Syariah, 2018)
The study focuses on the polemic of children vaccination among pro-vax and anti-vax groups. In addition, the study also discusses the use of vaccines against children according to the perspective of Islamic jurisprudence. To achieve that objective, this qualitative study combines library research based on documentation method and field study based on interview methods. The data obtained analyzed its content in a deductive and comparative method. The findings suggest that the Islamic jurisprudence regarding vaccination is necessary. This is because vaccine intake can prevent the risk of infection with vaccine prevention, thus reducing morbidity and mortality rates among children. In this regard, all parties need to get acquainted with the National Immunization Program through the provision of vaccines to children, and even as parents should consider holistic safety without selfishness. The effect of vaccination refusal can pose a risk to other children.